Inhibition of prostate cancer growth by solanine requires the suppression of cell cycle proteins and the activation of ROS/P38 signaling pathway. (10th October 2016) - Pan, Bin; Zhong, Weifeng; Deng, Zhihai; Lai, Caiyong; Chu, Jing; Jiao, Genlong; Liu, Junfeng; Zhou, Qizhao
Abstract: Solanine, a naturally steroidal glycoalkaloid in nightshade (Solanum nigrum Linn.), can inhibit proliferation and induce apoptosis of tumor cells. However, the mechanism of solanine‐suppressing prostate cancer cell growth remains to be elucidated. This study investigates the inhibition mechanism of solanine on cancer development in vivo and in cultured human prostate cancer cell DU145 in vitro. Results show that solanine injection significantly suppresses the tumor cell growth in xenograft athymic nude mice. Solanine regulates the protein levels of cell cycle proteins, including Cyclin D1, Cyclin E1, CDK2, CDK4, CDK6, and P21 in vivo and in vitro. Also, in cultured DU145 cell, solanine significantly inhibits cell growth. Moreover, the administration of NAC, an active oxygen scavenger, markedly reduces solanine‐induced cell death. Blockade of P38 MAPK kinase cannot suppress reactive oxygen species (ROS), but can suppress solanine‐induced cell apoptosis. Also, inhibition of ROS by NAC inactivates P38 pathway. Taken together, the data suggest that inhibition of prostate cancer growth by solanine may be through blocking the expression of cell cycle proteins and inducing apoptosis via ROS and activation of P38 pathway. These findings indicate an attractive therapeutic potential of solanine for suppression of prostate cancer. Abstract : Inhibition of prostate cancer metastasis by solanine may be through blocking the expression of cell cycle proteins and inducing apoptosis via induction of reactive oxygen species (ROS) and activation of P38 pathway. An attractive therapeutic potential of solanine for suppression of prostate cancer.